Fracionamento de silício em solos com diferentes históricos de cultivo - Silva, Helena Trindade da (2022)
Anthropogenic action directly interferes with our ecosystems. Although silicon dioxide (SiO2) is one of the most abundant compounds on Earth, there are several chemical forms found for this element in the soil and the effects of human action on the dynamics of silicon (Si) are still poorly understood. Thus, the objective of the present work was to evaluate whether the extraction and export of Si from the soil by annual agricultural cultivation over the years influences the content of the element in its different chemical forms present in the soil. In this sense, the levels of silicon in its different forms present in soils used for agricultural production for different times (2, 8 and 40 years) were quantified in comparison with the native field (control situation). The quantified forms of Si were: mobile fraction, adsorbed, associated with soil organic matter, occluded in Fe and Al sesquioxides and amorphous silica. The relationship of soil Si forms with possible changes in soil particle size and mineralogy was also studied through particle size and x-ray diffraction (XRD) analysis. The results obtained were analyzed using the linear model and the means were compared using the Tukey test (p < 0.05) of error probability when necessary. The proportion of Si forms is, in decreasing order: amorphous silica > Si bound to soil organic matter > Si adsorbed in the exchange complex > Si occluded in soil oxides > Mobile Si. The mobile Si fraction had its highest amount in the 40-year-old crop compared to the native field. The native grassland showed the highest amount of Si bound to soil organic matter and amorphous silica. Soil particles were larger for the native grassland. The cultivation times evaluated showed no change in soil mineralogy. It can be concluded that the evaluated agricultural system, over the years, changes the biogeochemical cycle of Si. Our results indicate that there is a need for soil fertility management that considers the Si element and its cycling. Also, the use of the soil with cultures accelerates the process of desilication by the extraction of the element and, consequently, the increase of soil weathering.